Comparative assessment of human chondroprogenitor viability and molecular phenotype in various parenteral transport media - Jeya Lisha John; Gurbind Singh; Ganesh Parasuraman; Abel Livingston; Grace Rebekah; Alfred Job Daniel; Solomon Sathishkumar; Elizabeth Vinod (Histochemistry and Cell Biology, 2025)

Comparative assessment of chondral defect repair using human bone marrow- and adipose tissue-derived mesenchymal stem cells, adult and foetal articular cartilage-derived chondrocytes, and chondroprogenitors: an ex-vivo model - Elizabeth Vinod; Ganesh Parasuraman; Jeya Lisha J.; Jithu James Varghese; Abel Livingston; Grace Rebekah; Deepak Vinod Francis; Solomon Sathishkumar; Alfred Job Daniel; Boopalan Ramasamy (Biotechnology Letters, 2025)

High dispersal ability versus migratory traditions: Fine‐scale population structure and post‐glacial colonisation in bar‐tailed godwits - Jesse R. Conklin; Yvonne I. Verkuil; Margaux J. M. Lefebvre; Phil F. Battley; Roeland A. Bom; Robert E. Gill; Chris J. Hassell; Job ten Horn; Daniel R. Ruthrauff; T. Lee Tibbitts; Pavel S. Tomkovich; Nils Warnock; et al. (Molecular Ecology, 2024)
In migratory animals, high mobility may reduce population structure through increased dispersal and enable adaptive responses to environmental change, whereas rigid migratory routines predict low dispersal, increased structure, and limited flexibility to respond to change. We explore the global population structure and phylogeographic history of the bar‐tailed godwit, Limosa lapponica , a migratory shorebird known for making the longest non‐stop flights of any landbird. Using nextRAD sequencing of 14,318 single‐nucleotide polymorphisms and scenario‐testing in an Approximate Bayesian Computation framework, we infer that bar‐tailed godwits existed in two main lineages at the last glacial maximum, when much of their present‐day breeding range persisted in a vast, unglaciated Siberian‐Beringian refugium, followed by admixture of these lineages in the eastern Palearctic. Subsequently, population structure developed at both longitudinal extremes: in the east, a genetic cline exists across latitude in the Alaska breeding range of subspecies L. l. baueri ; in the west, one lineage diversified into three extant subspecies L. l. lapponica , taymyrensis , and yamalensis , the former two of which migrate through previously glaciated western Europe. In the global range of this long‐distance migrant, we found evidence of both (1) fidelity to rigid behavioural routines promoting fine‐scale geographic population structure (in the east) and (2) flexibility to colonise recently available migratory flyways and non‐breeding areas (in the west). Our results suggest that cultural traditions in highly mobile vertebrates can override the expected effects of high dispersal ability on population structure, and provide insights for the evolution and flexibility of some of the world's longest migrations.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Neural entrainment is associated with subjective groove and complexity for performed but not mechanical musical rhythms - Daniel J. Cameron; Ioanna Zioga; Job P. Lindsen; Marcus T. Pearce; Geraint A. Wiggins; Keith Potter; Joydeep Bhattacharya (Experimental Brain Research, 2019)

Fungi, bacteria and soil pH : the oxalate–carbonate pathway as a model for metabolic interaction - Gaëtan Martin; Matteo Guggiari; Daniel Bravo; Jakob Zopfi; Guillaume Cailleau; Michel Aragno; Daniel Job; Eric Verrecchia; Pilar Junier (Environmental Microbiology, 2012)
Summary The oxalate–carbonate pathway involves the oxidation of calcium oxalate to low‐magnesium calcite and represents a potential long‐term terrestrial sink for atmospheric CO 2 . In this pathway, bacterial oxalate degradation is associated with a strong local alkalinization and subsequent carbonate precipitation. In order to test whether this process occurs in soil, the role of bacteria, fungi and calcium oxalate amendments was studied using microcosms. In a model system with sterile soil amended with laboratory cultures of oxalotrophic bacteria and fungi, the addition of calcium oxalate induced a distinct pH shift and led to the final precipitation of calcite. However, the simultaneous presence of bacteria and fungi was essential to drive this pH shift. Growth of both oxalotrophic bacteria and fungi was confirmed by qPCR on the frc (oxalotrophic bacteria) and 16 S rRNA genes, and the quantification of ergosterol (active fungal biomass) respectively. The experiment was replicated in microcosms with non‐sterilized soil. In this case, the bacterial and fungal contribution to oxalate degradation was evaluated by treatments with specific biocides (cycloheximide and bronopol). Results showed that the autochthonous microflora oxidized calcium oxalate and induced a significant soil alkalinization. Moreover, data confirmed the results from the model soil showing that bacteria are essentially responsible for the pH shift, but require the presence of fungi for their oxalotrophic activity. The combined results highlight that the interaction between bacteria and fungi is essential to drive metabolic processes in complex environments such as soil.

Selection of Grifola frondosa and Fomitopsis pinicola strains resistant to Trichoderma viride in teflon tubes confrontation method - Isabelle Schiff Giovannini; Daniel Job; Abdelaziz Hmamda (Mycological Progress, 2004)

Optimized fungal defibrillation of wood using selected strains of Gloeophyllum trabeum and Resinicium bicolor - Daniel Job (Mycological Progress, 2004)

Assessment of selected decay Basidiomycetes for selective biodefibrillation of Picea abies wood - Daniel Job (Mycological Progress, 2002)